2017
DOI: 10.3389/fneur.2017.00215
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Caged-GABA Rapidly Terminates Seizures In Vivo: Concentration and Light Intensity Dependence

Abstract: The therapy of focal epilepsy remains unsatisfactory for as many as 25% of patients. The photolysis of caged-γ-aminobutyric acid (caged-GABA) represents a novel and alternative option for the treatment of intractable epilepsy. Our previous experimental results have demonstrated that the use of blue light produced by light-emitting diode to uncage ruthenium-bipyridine-triphenylphosphine-c-GABA (RuBi-GABA) can rapidly terminate paroxysmal seizure activity both in vitro and in vivo. However, the optimal concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…As a nongenetic optical method, RuBi-GABA provides the property of high temporal and spatial resolution. Although, it has been utilized in many neuronal regulatory experiments [24][25][26], its effects are still limited by its fast drug metabolism. Hydrogels as one of the outstanding drug delivery carriers can form three-dimensional network to deliver drugs in various fields [34,35], and have been shown to perform excellent properties for neuromodulation according to our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a nongenetic optical method, RuBi-GABA provides the property of high temporal and spatial resolution. Although, it has been utilized in many neuronal regulatory experiments [24][25][26], its effects are still limited by its fast drug metabolism. Hydrogels as one of the outstanding drug delivery carriers can form three-dimensional network to deliver drugs in various fields [34,35], and have been shown to perform excellent properties for neuromodulation according to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 8(a) and (b) show the power components of spikes and LFPs in the 0-30 Hz frequency band during the three modulation periods, respectively, and the increased power in the frequency domain reflected enhanced neural activities. The frequency band of 0-30 Hz can be divided into five different frequency bands, including slow band (0-1 Hz), delta band (1-4 Hz), theta band (4-8 Hz), alpha band (8-13 Hz) and beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). As shown in figure 8, in the pre-seizure period, the power of both spikes and LFPs peaked at around 2 Hz in the delta band.…”
Section: Simultaneous Modulation Of Spikes and Lfps In Time And Frequ...mentioning
confidence: 99%
See 1 more Smart Citation
“…58 A previous study in pilocarpine-induced epilepsy rats reported that much of the increased preictal firing of neurons in the subiculum and CA1 correlated with preictal theta activity. 59 Furthermore, studies of rapid focal cooling 60 and photolysis of cage-GABA 61 in controlling seizures also demonstrated that theta band power reduction is a mechanistic marker for seizure reduction in these models. Several studies in other epilepsy models have found enhanced theta oscillations to be associated with reduced seizures 62,63 ; however, the correlation between the change in theta-band power and epileptic seizures needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2012) reported that RuBi-GABA with blue light could quickly terminate the seizure activity. In the years that followed, the team optimized the optimal concentration and light intensity of RuBi-GABA to achieve the best inhibition effect (Wang et al, 2017). RuBi-GABA contains a photolabile protecting group that can be removed by exposure to light.…”
Section: Introductionmentioning
confidence: 99%